Randomized pilot trial of ipratropium versus placebo in children with critical asthma. Issue 12 (21st October 2020) - Murphy, Kaitlyn; Mahmood, Nabihah; Craven, Daniel; Gallagher, John; Ross, Kristie; Speicher, Richard; Rotta, Alexandre T.; Shein, Steven L.
Abstract: Objective: To test the effects of inhaled ipratropium on clinical outcomes of critical asthma in the first randomized trial of this adjunctive therapy in critically ill children. Design: Pilot, placebo‐controlled, double‐blinded, and randomized‐controlled trial Patients: Thirty children (15 per group) with critical asthma receiving high‐intensity albuterol per a standardized pathway utilizing objective assessments to wean patients to less frequent albuterol administration. Interventions: Subjects were randomized to receive either nebulized ipratropium bromide (500 µg in 0.9% saline per dose) or an equivalent volume of nebulized 0.9% saline every 6 h until the patient was successfully weaned to albuterol doses every 2 h ("q2 albuterol"). Measurements and Main Results: Demographics, initial clinical severity score, and asthma histories were similar between groups. There was no significant difference in the median duration of high‐intensity albuterol between the treatment group (17.5 [10.3–22.1] h) and placebo group (14.6 [12.7–24.5] days; p = .56). Similarly, there was no significant difference in pediatric intensive care unit length of stay (22.6 [21.1–33.6] vs. 21.4 [16.1–35.8] h; p = .74) or hospital length of stay (48.0 [41.8–59.8] vs. 47.3 [37.2–63.1] h; p = .67). In multivariate linear regression adjusting for identified confounders, treatment with ipratropium was not significantly associated with any of the three outcomes. Side effects were rare and occurred with equally between both groups Conclusions: Adjunctive therapy with ipratropium was not associated with decreased duration of high‐intensity albuterol or shortened length of stay when compared to placebo. A larger, multicenter trial is warranted to confirm that ipratropium does not improve clinical outcomes.